Multidisciplinary care considerations for gender nonconforming adolescents with eating disorders: A case series. Issue 5 (8th May 2018) - Donaldson, Abigail A.; Hall, Allison; Neukirch, Jodie; Kasper, Vania; Simones, Shannon; Gagnon, Sherry; Reich, Steven; Forcier, Michelle
Abstract: Gender nonconforming youth are at risk for body dissatisfaction and disordered eating. Currently, only a small body of literature addresses this high‐risk group. The five cases in this series highlight important themes for this patient population from an interdisciplinary perspective. Identified themes include increased risk for self‐harm/suicide, complex psychiatric, and medical implications of delay to treatment for either gender dysphoria or disordered eating, and the importance of collaborative management to maximize care and facilitate healthy development to adulthood. The purpose of this case series is to expand the interdisciplinary discussion regarding the breadth of presentation and management considerations for gender nonconforming adolescents with disordered eating. An interdisciplinary approach to care might enhance access to comprehensive, collaborative treatment for disordered eating, and gender dysphoria in this unique population.